This is how they tell me the world ends ebook The cyberweapons arms race. - Perlroth, Nicole (2021)
THE NEW YORK TIMES BESTSELLER * Winner of the Financial Times & McKinsey Business Book of the Year Award * Bronze Medal, Arthur Ross Book Award (Council on Foreign Relations) "Written in the hot, propulsive prose of a spy thriller" ( The New York Times), the untold story of the cyberweapons market-the most secretive, government-backed market on earth-and a terrifying first look at a new kind of global warfare. Zero-day: a software bug that allows a hacker to break into your devices and move around undetected. One of the most coveted tools in a spy's arsenal, a zero-day has the power to silently spy on your iPhone, dismantle the safety controls at a chemical plant, alter an election, and shut down the electric grid (just ask Ukraine). For decades, under cover of classification levels and nondisclosure agreements, the United States government became the world's dominant hoarder of zero-days. U.S. government agents paid top dollar-first thousands, and later millions of dollars-to hackers willing to sell their lock-picking code and their silence. Then the United States lost control of its hoard and the market. Now those zero-days are in the hands of hostile nations and mercenaries who do not care if your vote goes missing, your clean water is contaminated, or our nuclear plants melt down. Filled with spies, hackers, arms dealers, and a few unsung heroes, written like a thriller and a reference, This Is How They Tell Me the World Ends is an astonishing feat of journalism. Based on years of reporting and hundreds of interviews, Nicole Perlroth lifts the curtain on a market in shadow, revealing the urgent threat faced by us all if we cannot bring the global cyberarms race to heel.